ANIMAL SPECIES SACRIFICED IN ANCIENT ROME AND CEREMONIAL PRACTICES - Katar, Murat (Dokuz Eylül Üniversitesi, 2026)
When looking at the history of humanity, it has be seen that from the earliest periods, people have been in search of faith and have done many things for their gods in the name of their beliefs. In ancient times, people sometimes built massive temples, sometimes waged wars for their gods, and sometimes organized ceremonies by sacrificing various animals as a form of gratitude to their gods or to draw closer to them. These sacrifice ceremonies that organised in ancient Roma had become not only a religious obligation but also a political and social event. This situation continues similarly today. Sacrificing for faith has turned into a ritual. Nowadays, people slaughter animals both for God and as a way of expressing thanks or gratitude to God when something good happens in their lives. In our society, this ritual, generally summarized by the expression “bloodletting,” has also transformed into a form of social solidarity through the distribution of the sacrificial meat. When this aspect is taken into consideration, it can be said that the act of sacrifice differs somewhat from other forms of worship. Sacrifice can be interpreted as a form of social assistance that extends to the whole of society. At the same time, it is observed that thanks to the continuation of the sacrifice tradition, agricultural activities have also developed.

İnsanlık tarihine bakıldığı zaman, en eski dönemlerden itibaren insanların bir inanç arayışında oldukları ve inançları uğruna da tanrıları için birçok şey yaptıkları görülmektedir. Eski dönemlerdeki insanlar kimi zaman devasa tapınaklar yaparken kimi zaman tanrıları için savaşmışlar, kimi zaman da tanrılarına bir şükür veya tanrıyla yakınlaşabilmek için çeşitli hayvanları kurban ederek törenler düzenlemişlerdir. Antik Roma döneminde düzenlenen bu kurban törenleri bir dini zorunluluktan öte aynı zamanda politik ve toplumsal bir etkinlik halini almıştı. Bu durum günümüzde de benzer şekilde devam etmektedir. İnanç için kurban kesilirken bu bir ritüele dönüşmüştür. Günümüzde hem tanrı için hem de hayatında bir güzel gelişme olduğu zaman insanlar tanrıya teşekkür veya şükür anlamında kurban kesmektedir. Bizim toplumumuzda genel anlamda “kan çıkarmak” tabiri ile özetlenen bu ritüel aynı zamanda kurbanın etinin dağıtılmasıyla beraber bir sosyal yardımlaşma biçimine dönüşmektedir. Bu özelliği dikkate alındığı zaman kurban ibadetinin diğer ibadetlerden biraz farkı olduğu söylenebilir. Kurban, toplumun geneline yansıyan sosyal bir yardımlaşma şeklinde yorumlanabileceği gibi aynı zamanda kurban adetinin devamı sayesinde zirai faaliyetler de gelişme gösterdiği görülüyor.
ANTİK ROMA’DA KURBAN EDİLEN HAYVAN TÜRLERİ VE TÖREN UYGULAMALARI
Keywords: Classical Greek and Roman History; Eski Yunan ve Roma Tarihi